Experimental and Numerical Investigation on the Triaxial Compressive Behavior of Steamed Recycled Aggregate Concrete - Yuzhi Chen; Yingjie Ning; Xudong Chen; Weihong Xuan; Xiangyi Zhu (Buildings, 2023)
The use of recycled aggregates to produce precast concrete products is conductive to the green development of construction industrialization. This paper aimed to study the effects of curing regimes and confining pressures on the triaxial compression behavior of recycled aggregate concrete (RAC). Triaxial compression tests were carried out on RAC under different curing regimes (standard curing, 60 °C—12 h and 80 °C—9 h), and the designed confining pressures were 0 MPa, 2.5 MPa, 5 MPa, and 10 MPa. The results show that the increase of confining pressure limits the expansion of cracks, causing the failure mode to change from vertical splitting to oblique shearing, and the triaxial compressive strength is doubled at most. Compared with standard curing, steam curing significantly weakened the triaxial compressive strength of RAC, which was related to the reduction of RAC cohesion, and the cohesion of RAC steam cured at 80 °C was reduced by 30%. The triaxial compression failure of RAC closely follows the Mohr–Coulomb criterion. Based on the discrete element method and test results, an RAC triaxial compression numerical model considering the shape of the actual coarse aggregate was established, and the propagation of cracks was discussed at the mesoscopic level.